The influence of the hippocampus and declarative memory on word use: Patients with amnesia use less imageable words - Hilverman, Caitlin (Neuropsychologia, 2017)
Hippocampal functioning contributes to our ability to generate multifaceted, imagistic event representations. Patients with hippocampal damage produce event narratives that contain fewer details and fewer imagistic features. We hypothesized that impoverished memory representations would influence language at the word level, yielding words lower in imageability and concreteness. We tested this by examining language produced by patients with bilateral hippocampal damage and severe declarative memory impairment, and brain-damaged and healthy comparison groups. Participants described events from the real past, imagined past, imagined present, and imagined future. We analyzed the imageability and concreteness of words used. Patients with amnesia used words that were less imageable than those of comparison groups across time periods, even when accounting for the amount of episodic detail in narratives. Moreover, all participants used words that were relatively more imageable when discussing real past events than other time periods. Taken together, these findings suggest that the memory that we have for an event affects how we talk about that event, and this extends all the way to the individual words that we use.